Pendampingan Pembelajaran Praktik Wudhu dan Sholat pada masa pandemi COVID 19 di MI Hidayatul Husna Butuh Kras kediri - Ida Apriliyanti; Khoirotul Izzah (LP3M IAIFA Kediri, 2021)
Learning is the acquisition of a subject or gaining a skill through lessons, experience or teaching. In the context of education, teachers teach so that learners can learn and complete the content of the lesson to achieve a determined objective (cognitive aspect) can also affect changes in attitude (affective aspects) and skills (psychomotor aspects) as students, but this teaching process gives the impression only as the work of one party, namely teaching work only. The success of achieving the competence of one subject depends on several aspects. One of them is practical material. A very influential aspect is how a teacher carries out learning. The tendency to learn today is still centered on teachers by telling stories or preaching. Students are less actively involved in the learning process. The tendency to learn today is still centered on teachers by telling stories or preaching. Students are less actively involved in the learning process. As a result, students' level of understanding of the subject matter is low. In the practice of ablution and prayer this is called an activity that was created in dealing with the lack of religious knowledge. The ability of ablution and prayer introduces and directs learners to become sholeh / sholehah children, so as to be able to apply it in schools and communities. Everyone who will pray will make ablution first. There are still many researchers looking at children or people who are perfunctory or imperfect. The research was conducted in August 2021, researchers this time took the theme of learning wudhu and prayer practices to have the goal that later students kela VI MI Hidayatul Husna can carry out their obligations properly and correctly, so that what we teach them can benefit people's lives or the life to come.